A forgotten epidemic that changed medicine: measles in the US Army, 1917–18. Issue 7 (July 2015) - Morens, David M; Taubenberger, Jeffery K
Summary A US army-wide measles outbreak in 1917–18 resulted in more than 95 000 cases and more than 3000 deaths. An outbreak investigation implicated measles and streptococcal co-infections in most deaths, and also characterised a parallel epidemic of primary streptococcal pneumonia in soldiers without measles. For the first time, the natural history and pathogenesis of these diseases was able to be well characterised by a broad-interdisciplinary research effort with hundreds of military and civilian physicians and scientists representing disciplines such as internal medicine, pathology, microbiology, radiology, surgery, preventive medicine, and rehabilitation medicine. A clear conceptualisation of bronchopneumonia resulting from viral–bacterial interactions between pathogens was developed, and prevention and treatment approaches were developed and optimised in real time. These approaches were used in the 1918 influenza pandemic, which began as the measles epidemic waned. The outbreak findings remain relevant to the understanding and medical management of severe pneumonia.